Electrophysiological observations on the effects of potassium ions on the response of intradental nerves to dentinal tubular flow in the cat - S. Wanachantararak (2018)
Objective: To determine the effects of K+on the sensitivity of sensory receptors in teeth to fluid flow through dentine. Methods: Evoked discharges were recorded from intradental nerves in anaesthetised cats during the application of 5 s hydrostatic pressure stimuli to exposed dentine through either normal Ringer's or Ringer's containing up to 255 mmol/l K+. The stimuli ranged between -500 and +500 mm Hg. Results: The number of impulses evoked by a positive pressure stimulus increased, and the latency of the response decreased, as either the pressure or the K+concentration of the Ringer's was increased. The response to a negative pressure stimulus applied 2 s after a positive pressure pulse of equal but opposite amplitude decreased as either the intensity of the stimulus or the K+concentration of the Ringer's was increased. Conclusions: Potassium ions that were transported into the dentine and pulp by bulk flow during the application of positive pressure stimuli increased the sensitivity of the receptors to inward tubular flow but decreased their sensitivity to outward flow. © 2010 Elsevier Ltd.